Strengthening Digital Marketing and Social Ties for Sustainable Economic Growth and Community Well-being - Indrawati, Indrawati (ADPEBI, 2024)
This paper explores the pivotal role of digital marketing and social ties in driving sustainable economic growth and enhancing community well-being in Indonesia. As Indonesia aims to become the world’s 6th largest economy by 2028, leveraging advancements in communication and information technology is crucial. The paper highlights the benefits of digital marketing for SMEs, including broader reach, precise targeting, cost efficiency, and enhanced customer engagement. Despite these advantages, only 16% of SMEs have adopted digitalization, underscoring the need for increased support and education. The paper also emphasizes the importance of social ties in fostering economic activities and community resilience. Strong social networks provide emotional support, enhance community engagement, and facilitate economic transactions. Examples such as the Mondragón Corporation in Spain and Aruna in Indonesia illustrate how social cohesion can lead to economic success. The paper concludes with practical solutions to strengthen social ties, including community engagement, education programs, and inclusive policy-making, aiming to create a more resilient and prosperous society.